Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar Siswa Kelas X SMA Swasta Sinar Pancasila Betun - Mario Nahak; Wolfgang Asindo Seran; Rosalia Mulyani; Ivony Sarlin Asa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of the application of the Discovery Learning learning model on student learning outcomes in Geography class X at Sinar Pancasila Betun Private High School. The study used an experimental method with a pretest-posttest control group design. The study population was all students of class X, with a purposive sampling technique consisting of an experimental class and a control class. The research instrument was a multiple-choice learning outcome test that had been tested for validity and reliability. The results showed a significant increase in learning outcomes in the experimental class after the application of the Discovery Learning learning model. The average posttest score of the experimental class was 74.0236, higher than the control class of 19.2045. Hypothesis testing using the t-test showed that the calculated t value > t table at a significance level of 5%, so the alternative hypothesis was accepted. This means that there is a positive effect of the use of the Discovery Learning learning model on student learning outcomes. Based on these findings, it is concluded that the Discovery Learning learning model is effective for improving student learning outcomes in Geography learning and can be used as an alternative innovative learning strategy in schools.